Association of CYP2A6 gene related to the characteristic carcass, commercial cuts, quality of meat and cholesterol of lamb meat - Istiqlal, R. F.; Listyarini, K.; Jakaria, J.; Budiman, C.; Gunawan, A. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
As meat-producing livestock, sheep are a benchmark for communities seeking quality and healthy meat. The CYP2A6 gene has emerged as a potential tool for improving lamb meat quality. This study investigated the genetic variability of the CYP2A6 gene and its association with key determinants of lamb meat quality. The research involved 140 male sheep from five breeds: Javanese thin-tail sheep (JTTS), Garut sheep (GS), Jonggol sheep (JS), Barbados cross sheep (BCS), and Compass agrinak sheep (CAS). PCR-RFLP was employed to identify CYP2A6|BsmAI gene polymorphism and the general linear model (GLM) was used to analyze the gene's association with meat quality. The results showed a polymorphism in the CYP2A6 gene (SNP g.49170107 G>T), presenting two genotypes: GG and GT. The analysis results demonstrated that the CYP2A6 gene (P<0.05) significantly correlates with carcass characteristics (live weight, hot carcass weight, carcass percentage, cold carcass weight), commercial cuts, physical meat quality, and cholesterol content. The GT genotype exhibited superior meat quality to the GG genotype, suggesting that the CYP2A6 gene could serve as a valuable genetic marker for enhancing lamb meat quality.